Islamic Students’ Understanding of Menstruation, Postpartum, and Istihadhoh: Pemahaman Mahasiswa Islam tentang Menstruasi, Pasca Melahirkan, dan Istihadhoh - Maghfiroh, Ahlul; Moch. Bahak Udin By Arifin (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Menstruation, postpartum bleeding, and istihadhoh are essential biological and religious aspects in women’s lives, directly influencing health and Islamic worship practices. Specific background: In Islamic boarding schools, female students are expected to master this knowledge as part of their daily practice of purity and ibadah. Knowledge gap: Previous studies have mostly focused on adult women, while there is limited evidence on how female students in pesantren understand these issues. Aims: This study investigates the level of understanding of female students at Darussalamah Islamic Boarding School, Sidoarjo, regarding menstruation, postpartum bleeding, and istihadhoh. Results: Findings indicate that 100% of respondents understood the definitions of menstruation and postpartum bleeding, while 14% were unclear about istihadhoh. Furthermore, 16% of students did not fully comprehend prohibitions during postpartum. Novelty: This study highlights the integration of Islamic jurisprudence with reproductive health education within pesantren curricula, combining traditional and digital learning sources. Implications: The results suggest the need for more interactive discussions and simplified teaching materials to strengthen comprehension and ensure students can practice worship correctly while raising reproductive health awareness in pesantren contexts. Highlight & Keyword Highlights : Students show strong knowledge of menstruation and postpartum but gaps in istihadhoh Education integrates classical Islamic texts with digital learning resources Findings support curriculum development in Islamic boarding schools Keywords : Mestruation, Postpartum, Istihadhoh, Islamic Education, Pesantren